PENGARUH WAKTU PENGUKUSAN JAGUNG KUNING HIBRIDA DAN LAMA PENYIMPANAN DINGIN SUSU KEDELAI JAGUNG TERHADAP SIFAT FISIK DAN ORGANOLEPTIKNYA - Loekito, Okky Purnama; Marsono, Yustinus; Srianta, Ignatius (Widya Mandala Surabaya Catholic University, 2013)
Soycorn milk is a beverage from soybean and corn combination. Ratio of soybean and corn is 70:30. The addition of corn reduce beany flavor from soy milk. The starch content in corn affects physical and sensory properties of corn soy milk. Corn starch characteristics change during processing. This study aimed to evaluate the steaming duration of yellow hybrid corn and cold storage time of soycorn milk that obtain soycorn milk with physical and sensory properties that favored by consumers. The results showed steaming duration of yellow hybrid corn and cold storage time of soycorn milk affected its TSS, colloidal stability, and viscosity. The longer corn steaming duration, it increased TSS (9,01%), colloidal stability (2,57%), and viscosity (18,56%) of soycorn milk. The cold storage time of soycorn milk increased its TSS (14,15%) and viscosity (22,11%), whereas the colloidal stability decreased 6,21%. Steaming duration of yellow hybrid corn and cold storage time of soycorn milk affected level preferences for viscosity but did not affect the level preferences for color and flavor of soycorn milk.